Catalytic roles of Sm2O3dopants on ethylene oxide sensing mechanisms of flame-made SnO2nanoparticles - Suparat Singkammo (2018)
© 2018 Elsevier B.V. In this work, Sm2O3-doped SnO2nanoparticles containing 0.1–2 wt% Sm were produced in a single step by flame spray pyrolysis (FSP) technique for the first time and their catalytic properties were systematically investigated for ethylene oxide (C2H4O) detection. The morphology and structure of the nanoparticles were characterized by various X-ray/electron microscopic and spectroscopic analyses. The sensing films were fabricated by a spin-coating process and the gas sensing performances were studied towards C2H4O at the operating temperatures ranging from 200 to 400 °C in dry air. It was found that the optimal Sm concentration of 0.5 wt% led to the highest sensor response of 61.9 towards 30 ppm C2H4O, which was about an order of magnitude higher than that of the undoped sensor at the optimal operating temperature of 350 °C. Moreover, the optimal Sm2O3-doped SnO2sensor displayed high C2H4O selectivity against H2, H2S, C2H6O, C2H2, NO and NO2. The enhanced gas-sensing performances of Sm2O3-doped SnO2nanoparticles were found by the response rate analysis to be attributed to the amplified reaction rate constant for ethylene oxidation by the Sm2O3catalyst.